2012
DOI: 10.1016/j.bbapap.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of D-serine dehydratase from Escherichia coli

Abstract: D-Serine dehydratase from Escherichia coli is a member of the β-family (fold-type II) of the pyridoxal 5'-phosphate-dependent enzymes, catalyzing the conversion of D-serine to pyruvate and ammonia. The crystal structure of monomeric D-serine dehydratase has been solved to 1.97Å-resolution for an orthorhombic data set by molecular replacement. In addition, the structure was refined in a monoclinic data set to 1.55Å resolution. The structure of DSD reveals a larger pyridoxal 5'-phosphate-binding domain and a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The resulting PLP-aminoacrylate intermediate undergoes nucleophilic attack by K41 at C4′, and the resulting tetrahedral gem-diamine intermediate collapses to yield amino acrylate and enzyme-bound PLP; aminoacrylate then undergoes nonenzymatic hydrolysis to yield pyruvate and ammonia. 49 …”
Section: Ppi and Pi In General Acid-general Base Catalysismentioning
confidence: 99%
“…The resulting PLP-aminoacrylate intermediate undergoes nucleophilic attack by K41 at C4′, and the resulting tetrahedral gem-diamine intermediate collapses to yield amino acrylate and enzyme-bound PLP; aminoacrylate then undergoes nonenzymatic hydrolysis to yield pyruvate and ammonia. 49 …”
Section: Ppi and Pi In General Acid-general Base Catalysismentioning
confidence: 99%
“…However, an alignment of DsdA [19080] with all DsdA sequences from the studied P. pentosaceus strains and DsdA from E. coli showed that at position 67 a threonine residue is replaced with an alanine residue and at position 278 a proline residue is replaced with a leucine residue. The latter amino acid substitution lies next to the so-called tetraglycine loop (residues G279, G281, G282, and G283 in DsdA from E. coli), which is conserved in PLP-dependent enzymes and is involved in the binding of PLP (30). Therefore, we think that the binding of PLP is impaired in DsdA from P. pentosaceus FAM19080.…”
Section: Discussionmentioning
confidence: 99%
“…Figure S1(A) shows the sequence alignment of DAPAL with DSD and SR carried out using CLUSTAL W. All three enzymes catalyze single substrate reactions and can use serine as a substrate. The N1 of PLP is hydrogen bonded to a serine residue in DSD and SR [6,23]. However, in DAPAL, the equivalent residue is a threonine.…”
Section: Mutation Of Thr385: Residue Interacting With N1 Of Plpmentioning
confidence: 99%
“…Enzymes of the fold‐type II family carry out β‐elimination and β‐replacement reactions and share a low level of amino acid sequence identity (< 20%). Well‐characterized enzymes from this family are tryptophan synthase‐β subunit (TrpS; http://www.chem.qmul.ac.uk/iubmb/enzyme/EC4/2/1/20.html) , d ‐serine dehydratase (DSD; http://www.chem.qmul.ac.uk/iubmb/enzyme/EC4/3/1/17.html) , cystathionine‐βsynthase (CBS; http://www.chem.qmul.ac.uk/iubmb/enzyme/EC4/2/1/22.html) , O ‐acetylserine sulfhydrylase (OASS; http://www.chem.qmul.ac.uk/iubmb/enzyme/EC4/2/99/8.html) , threonine deaminase (http://www.chem.qmul.ac.uk/iubmb/enzyme/EC4/3/1/19.html) , d ‐cysteine desulfhydrase (http://www.chem.qmul.ac.uk/iubmb/enzyme/EC4/4/1/15.html), etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation